First Report of Pestalotiopsis populi-nigrae on Poplar in North America - Newcombe, G (Plant disease, 2000)
Black acervuli were observed on abaxial surfaces of leaves of hybrid poplar (Populus trichocarpa Torr. & A. Gray × P. deltoides Marsh.) collected during fall 1998 in western Washington. Melampsora uredinia also were present but may be coincidental. When incubated in a moist petri dish, leaves became necrotic, and acervuli produced black masses of fivecelled, appendage-bearing conidia. Average conidia length was 25 µm. Three median versicolorous cells averaged 17.5 µm long and 6 µm wide; the upper two were darker than the lower one. There were typically three apical setulae, averaging 20 µm long. The average basal pedicel was 5 µm long. The fungus fits the description of Pestalotiopsis populi-nigrae (Sawada et Ito) Morelet. Originally described as an opportunistic pathogen on poplar in Japan (1), P. populi-nigrae was subsequently found on poplar in Europe (2). It is also the cause of cane blight of Rosa spp. in Japan (2), but it has never been reported in North America. A specimen has been deposited in the U.S. National Fungus Collections (BPI 746460). I did not observe P. populi-nigrae in 1997 to 1999 collections of rusted poplar leaves from the Southeast, western Kentucky, Minnesota, and Iowa nor in other Pacific Northwest collections. This was not a comprehensive survey for P. populi-nigrae but may indicate that the fungus is rare in North America. It also is possible that BPI 746460 represents an undescribed, uncommon species native to North America that is morphologically indistinguishable from P. populi-nigrae. Further research is required to test this hypothesis. References: (1) K. Ito. Bull. Gov. For. Exp. Stn. 45:135, 1950. (2) E. Kimishima et al. Ann. Phytopathol. Soc. Jpn. 62:502, 1996